Damage identification in masonry structures with vibration measurements - Ramos, Luís F. (2008)
The paper aims at exploring damage assessment in masonry structures at an early stage by vibration measurements. For this purpose, one approach is proposed combining global and local ND methods. To further evaluate the approach, one masonry tower in Portugal was studied together with one wall model in the laboratory. The model was built as reference, undamaged, state. Afterwards, progressive damage was induced and sequential modal identification analysis was performed at each damage stage, aiming to find adequate correspondence between dynamic behavior and internal crack growth. The paper presents all the analyses carried out with the aim to detect and locate the damage by means of vibrations measurements.